Development of prefabricated modular retrofitting solution for post-World War II buildings - Borodinecs, Anatolijs; Zemitis, Jurgis; Dobelis, Modris; Kalinka, Maris; Geikins, Aleksandrs (International Conference “Environmental Engineering”, 2017)
Residential and public buildings are one of the essential energy consumers. The majority of European buildings were constructed within the period from mid-1950ies to the late 1990ies. Currently the retrofitting process is too slow. The main barriers are complicated retrofitting process, variety of available technologies as well as precision of estimated energy savings calculations. This paper is prepared in scope of work done within the European Regional Development Fund project “NEARLY ZERO ENERGY SOLUTIONS FOR UNCLASSIFIED BUILDINGS”. The main aim of this study is to develop full modular retrofitting process based on 3D laser scanning minimizing time consumed for architectural project development, on-site construction works as well as to ensure correct energy simulation. Paper presents results of Latvian case building 3D scanning results, architectural project development specifics as well as selection of optimal thermal insulation layout and energy simulations. Study analyses main barriers for wide implementation of prefabricated panels.